(3ZjK GdehGgH GdYdjI TQM GdMce GdYWGFjIs - (3GHf YHGO, eMeO Hf EHQGgje Hf YHO Gddg, J(B792(3g`s ((3OGQ GdfOhI HGdeSLO GdMQGes)
(3ChdgG (B:s
(3fGbU GdChd, hChdg(B: (3fU YHOg CeO bdHg HLfhOg hbWY Yf faSg eOO LfhOgG hEPG CQGO NPdGf YHOg aYdi GdYcSs
(3BNQgG (B:s
(3jYed Ydi NdGU faSg hdG jdReg GJHGY eQVGJ ZjQg abO bjd QVi GdfGS ZGjI dG JOQc hfMf fQZH Edi ef hbY HgPg GdJCdjas
(3aj BNQgG fbhd hCMGOjK aj bJd GdhRZIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 299s
(3eYLe GdeDdajf(B: 3 / 34s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs